PHOTO CHROMATIC SENSORS OF MULTINARY MIXED VALENCE INORGANIC MICRO NEEDLES - Kledi Xhaxhiu; Carita Kvarnström; Pia Damlin; Arjan Korpa; Klaus Bente (Journal of Engineering & Processing Management, 2013)
The recent I-U measurements on the individual micro needle-shaped crystals, of the ternary mixed valence compound In5Se5Cl, crystallizing in the monoclinic crystal system (P21/m), showed significant light sensitivities. Micro needles of In5Se5Cl "glued" on Si- and Cu- substrates were measured under five different wavelengths with various irradiation intensities to investigate their photo chromatic sensing behavior along with the substrate’s influence. In the measuring voltage range 0 - 3 V and maximal LED illumination intensity, current jumps above two orders of magnitude were observed for white light (4100 K; 200 lm), followed by the blue light (460 nm; 976 mW). The amber light (590 nm; 203 mW) exhibited the lowest response. Green- and blue light were selected to determine the substrate&amp's effect. The micro-needles chips prepared with Si-substrates displayed higher currents for the same voltages in comparison to those prepared with Cusubstrates. These differences decreased with the voltage increase for both employed wavelengths. The mutual structural substitution of a selenium with sulfur, led to the compound In5Se4Cl. The later crystallizes similarly to In5Se5Cl. Its I-U measurements recorded with green and blue light, on Cu-substrate chips within the voltage range 0 -3 V, revealed more pronounced photo chromatic sensorial for both wavelengths used. These differences increased with the voltage increase for both employed wavelengths. At 3 V, current increases up to 2.2 times and 2.4 times were observed for the green light and blue light respectively. Typically high and better distinguishable sensorial activity was observed for all the employed wavelengths using chips with In5Se4Cl crystals on Cu-substrate, even at minimal irradiation LED power (0.25 %). The micro-reflection measurements of both needle-shaped crystals displayed a substitution dependent band-gap. For In5Se5Cl the band gap was estimated at 580 nm. Thickness interference oscillations strongly damped due to structural inhomogeneity or defect-related absorption suggest two possible band gaps for In5Se4Cl; at 540 nm or at 620 nm.
Keywords: Photo chromatic sensors; micro needles; sensorial activity; substrate influence; substitution influence